Response of yearling cattle to burning and fertilizing bluestem pasture and intensively stocking early - E.F. Smith; B. Schalles; L. Harbers; R. Pruitt; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1978)
Long term (28 years) annual, late spring burning of bluestem pasture produced the most daily gain of all pasture treatments but not significantly more than stocking intensively early. Nitrogen applied to a late-spring-burned pasture did not significantly increase daily cattle gains over those from a similarly burned pasture not fertilized. But the nitrogen increased gain per acre by increasing carrying capacity of the pasture. Performance of animals on pasture stocked at twice the normal rate the first half of the season (intensive stocking early) did not differ from performance under normal stocking (burned with no nitrogen added) for the entire season. But for the period April 28 to July 15 intensive stocking early was superior in rate of gain and gain per acre. Pastures burned annually produced better range plant composition than unburned pastures. The best range plant composition was on the pasture intensively stocked early.
Keywords: Cattlemen& #x27; s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Yearling cattle; Fertilizer; Daily gain